The effectiveness of the physical therapy programme on the dynamometry and power index of the upper extremities of patients with rheumatoid arthritis - A. Nogas (Journal of Education, Health and Sport, 2021)
The purpose of the paper is to determine the effectiveness of the physical therapy programme on the dynamometry and power index of the upper extremities of patients with rheumatoid arthritis. Materials and methods. A total of 188 patients with rheumatoid arthritis were examined, including 156 women (83%) and 32 men (17%), with an average age of 45 years. All patients were randomly assigned to the control (n=92) and intervention (n=96) groups. Patients in the control group underwent rehabilitation in accordance with the recommendations of the regulatory document of the Ministry of Health of Ukraine. The subjects of the main group were engaged in the proposed technology of rehabilitation measures with a personalised approach to each patient, in accordance with the domains of the ICF, taking into account the factors influencing the level of functional impairment. Dynamometry was used to determine the strength of the hand flexor muscles of the affected upper extremities. The strength index of the hand muscles (relative strength index) was calculated in percentage, which is important for assessing the functional ability of the affected limb. The difference in means was considered significant at p<0.05. The obtained digital material was processed statistically using the Statistica 10 statistical analysis package (Serial Number: STA999K347150-W). Results. Both standard treatment and physical therapy after 3 months contributed to the improvement of dynamometry and power index in the affected upper limbs of all patients. However, in patients of the main group, the changes were more pronounced than in patients of the control group, where the indicators were lower. After 6 months of physical therapy, there was a significant improvement in muscle strength in patients of the main group: in the right limb it increased from 32.8±3.5 kg to 36.6±4.0 kg, in the left – from 28.5±3.52 kg to 32.2±3.5 kg (p<0.05). Patients in the control group also showed an increase in muscle strength in both limbs (from 30.7±3.3 kg to 33.2±3.1 kg in the right to 25.8±3.7 kg to 28.1±3.6 kg in the left), but the dynamometry values were significantly lower. Accordingly, the power index of the right limb in patients of the main group increased from 42.1% to 48.9%, the left limb – from 36.2% to 42.1%, which is significantly higher than in patients of the control group - from 39.3% to 44.5% (right limb) and from 33.4% to 37.8% (left limb) (p<0.05). Conclusion. Both standard treatment and physical therapy after 3 and 6 months contributed to the improvement of dynamometry and power index in the affected upper extremities of all patients. However, in patients of the main group, the changes were more pronounced than in patients of the control group, where the indicators were significantly lower, which confirms the effectiveness of the implemented rehabilitation measures.